Komplikasi Bayi Baru Lahir ditinjau dari Kejadian Positif Covid-19 pada Ibu Bersalin - Monika Herti Kurniasari; Ratna Dewi; Diah Eka Nugraheni (Universitas Baiturrahim, 2023)
Data on maternal mortality in Brazil 20 mothers died of COVID-19 where 12 cases were during pregnancy (60%), 3 cases were postpartum (15%), 1 case was a cesarean section delivery (5%) and 4 data were not reported. This condition illustrates the high risk of the mother during pregnancy and childbirth against Covid-19. Various efforts have been made by the government to prevent transmission of COVID-19, especially to pregnant and maternity women. This study was conducted to determine the effect of the positive incidence of COVID-19 in maternity on BBL complications at Dr. RSUD. M. Yunus Bengkulu City in 2021. This type of research is a retrospective method. The population in this study were all babies born in RSUD Dr. M. Yunus, Bengkulu city, in 2021, totaling 118 babies were born, with 22 of them experiencing complications. The sample in this study was divided into two groups, 22 cases were taken by total sampling and the control group was taken with a ratio of 1:1 by systematic random sampling. Data analysis was carried out univariate and bivariate with chi square test. The results of the chi square test showed a value of 0.015 (<0.05) meaning the effect of positive cases of covid-19 on mothers giving birth with complications in BBL. It is hoped that the hospital will prepare special detection and treatment for maternity mothers who are positive for Covid-19 to prevent and manage possible complications of BBL